Relative Circulating Autoantibodies IgA/IgG to Tissue Transglutaminase and Deamidated Gliadin with Celiac Disease Patients - Abd-Almajeed, Saif Ali; Mosa, Zahraa Safaa-Alden (Medical Science Journal for Advance Research, 2025)
Background: Celiac disease (CD) is an immune-mediated condition characterized by small intestinal enteropathy, systemic symptoms related to malabsorption or immune activation, and autoantibodies to tissue transglutaminase (TTG). The disease may present with a wide spectrum of symptoms, such as diarrhea, abdominal pain, involuntary weight loss, bloating, fatigue, anemia, and vitamin deficiencies. Aim of Study: To evaluate the serological test (anti-tissue transglutaminase, anti-gliadin peptides Ab IgG, IgA) in Al-Diwaniyah city. Methods: Method included designing a study on 150 patients and controls (both sexes and ages from 2 to 10 years) divided into three groups. One group included 30 control and the other included 30 patients with CD at diagnosis, on a gluten containing diet (newly diagnosed); group 2 consisted of 30 patients on a Gluten Free Diet ( GFD) for at least 1 year (GFD); group 3 consisted of 60 controls (control) and clinic private. Serological analysis was carried out on the serum samples to quantitatively measure the presence of circulating autoantibodies IgA/IgG to tissue transglutaminase and deamidated gliadin by the indirect enzyme-linked immunosorbent assay technique using antibody specific (ELISA) kits. Results: the percentage of positive results from four serological tests: Anti-gliadin IgA, Anti-gliadin IgG, Anti-tTG IgA, and Anti-tTG IgG. Anti-gliadin IgA shows the highest positivity rate (100%), indicating strong diagnostic relevance. Anti-gliadin IgG and Anti-tTG IgA have moderately lower positivity rates, while Anti-tTG IgG shows the lowest but still significant positivity. SEM error bars ensure statistical reliability. The results emphasize the importance of anti-gliadin IgA as a key diagnostic marker for celiac disease. Conclusion: Estimation of anti-tissue transglutaminase and anti-gliadin peptides Ab IgG and IgA in ELISA assay was considered as a screening test.